2000
DOI: 10.1073/pnas.97.9.4844
|View full text |Cite
|
Sign up to set email alerts
|

15-Deoxy-Δ 12,14 -prostaglandin J 2 inhibits multiple steps in the NF-κB signaling pathway

Abstract: Prostaglandin J2 (PGJ2) and its metabolites ⌬ 12 -PGJ2 and 15-deoxy-⌬ 12,14 -PGJ2 (15d-PGJ2) are naturally occurring derivatives of prostaglandin D2 that have been suggested to exert antiinflammatory effects in vivo. 15d-PGJ 2 is a high-affinity ligand for the peroxisome proliferator-activated receptor ␥ (PPAR␥) and has been demonstrated to inhibit the induction of inflammatory response genes, including inducible NO synthase and tumor necrosis factor ␣, in a PPAR␥-dependent manner. We report here that 15d-PGJ2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

41
756
8
6

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 962 publications
(811 citation statements)
references
References 34 publications
41
756
8
6
Order By: Relevance
“…One attractive hypothesis lies in the possible blockage of I B degradation or phosphorylation by pioglitazone (18). Finally, and as has been previously 2296 BOILEAU ET AL reported (47), the effect of pioglitazone may also be possibly explained by the inhibition of DNA binding of the p65 NF-B subunits. In summary, this study provides new information on the potential DMOAD effects of PPAR␥ agonists.…”
Section: Discussionmentioning
confidence: 75%
“…One attractive hypothesis lies in the possible blockage of I B degradation or phosphorylation by pioglitazone (18). Finally, and as has been previously 2296 BOILEAU ET AL reported (47), the effect of pioglitazone may also be possibly explained by the inhibition of DNA binding of the p65 NF-B subunits. In summary, this study provides new information on the potential DMOAD effects of PPAR␥ agonists.…”
Section: Discussionmentioning
confidence: 75%
“…Rossi et al reported the direct inhibition of inhibitor of nuclear factor B (NF-B) kinase activity by 15deoxy-PGJ 2 (29). However, Straus et al demonstrated that 15deoxy-PGJ 2 may reduce NF-B binding by alkylating p50/p65 dimers through PPAR␥-dependent pathways (30). Thus, 15deoxy-PGJ 2 appears to inhibit NF-B activation at different levels and may exert its activity in a PPAR␥-dependent and -independent manner.…”
Section: Discussionmentioning
confidence: 99%
“…169 -172 The anti-inflammatory effect of 15d-PGJ2 is mediated at least in part through suppression of STAT expression and a resultant increase in I B expression, leading to decreased nuclear translocation of NF-B and thus decreased NF-B transcription activity. 169,173 Moreover, at high concentrations 15d-PGJ2 induces apoptosis in activated microglia. 172 Cerebral ischemia increases PPAR␥ expression in neurons and microglia, but at the same time DNA binding of PPAR␥ is reduced.…”
Section: Ppar␥mentioning
confidence: 99%